Thermodynamic Characteristics of Compressed Air in Salt Caverns of CAES: Considering Air Injection for Brine Drainage - Shizhong Sun; Bin Wu; Yonggao Yin; Liang Shao; Rui Li; Xiaofeng Jiang; Yu Sun; Xiaodong Huo; Chen Ling (Energies)
The air injection for brine drainage affects the thermodynamic characteristics of salt caverns in the operation of compressed air energy storage (CAES). This study develops a thermodynamic model to predict temperature and pressure variations during brine drainage and operational cycles, validated against Huntorf plant data. Results demonstrate that increasing the air injection flow rate from 80 to 120 kg/s reduces the brine drainage initiation time by up to 47.3% and lowers the terminal brine drainage pressure by 0.62 MPa, while raising the maximum air temperature by 4.9 K. Similarly, expanding the brine drainage pipeline cross-sectional area from 2.99 m2 to 9.57 m2 reduces the total drainage time by 33.7%. Crucially, these parameters determine the initial pressure and temperature at the completion of brine drainage, which subsequently shape the pressure bounds of the operational cycles, with variations reaching 691.5 kPa, and the peak temperature fluctuations, with differences of up to 4.9 K during the first cycle. This research offers insights into optimizing the design and operation of the CAES system with salt cavern air storage.